2007
DOI: 10.1016/j.neuroscience.2006.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β vaccination, but not nitro-nonsteroidal anti-inflammatory drug treatment, increases vascular amyloid and microhemorrhage while both reduce parenchymal amyloid

Abstract: Vaccination with Aβ 1-42 and treatment with NCX-2216, a novel nitric oxide releasing flurbiprofen derivative, have each been shown separately to reduce amyloid deposition in transgenic mice and have been suggested as potential therapies for Alzheimer's disease. In the current study we treated doubly transgenic amyloid precursor protein and presenilin-1 (APP+PS1) mice with Aβ 1-42 vaccination, NCX-2216 or both drugs simultaneously for 9 months. We found that all treatments reduced amyloid deposition, both compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 44 publications
5
76
1
Order By: Relevance
“…Although not statistically significant, there was nonetheless approximately a 41% increase compared with the control group, and these data resemble the results generated by (Wilcock et al, 2007) with APPϩPS1 aged mice. Thus, immunization with the second generation epitope vaccine did not increase the incidence of cerebral microhemorrhages in ϳ19-month-old APP Tg 2576 mice (Fig.…”
Section: The Effect Of Vaccination On Microglial Activation Lymphocysupporting
confidence: 84%
See 2 more Smart Citations
“…Although not statistically significant, there was nonetheless approximately a 41% increase compared with the control group, and these data resemble the results generated by (Wilcock et al, 2007) with APPϩPS1 aged mice. Thus, immunization with the second generation epitope vaccine did not increase the incidence of cerebral microhemorrhages in ϳ19-month-old APP Tg 2576 mice (Fig.…”
Section: The Effect Of Vaccination On Microglial Activation Lymphocysupporting
confidence: 84%
“…It is known that AN-1792 vaccine caused an increase in cerebral vasculature deposition of A␤ (Masliah et al, 2005;Nicoll et al, 2006;Patton et al, 2006). Previously it was also shown that active A␤ 42 vaccination of double transgenic (APPϩPS1) mice resulted in significantly increased cerebral amyloid angiopathy and associated microhemorrhages (Wilcock et al, 2007). Although we did not directly investigate the effect of epitope vaccine on A␤ deposition in cerebral vasculature, we demonstrated that anti-A␤ 1-11 antibodies did not increase the incidence of cerebral microhemorrhages in the brains of immunized mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory response is the reaction to resist pathologic alterations, which demonstrated that inflammation plays a vital role in influencing AD. 20 Studies have verified that the effects of inflammatory response are double-sided. Microglial are activated, releasing harmful inflammatory factors, whereas inflammatory factors induce phagocytosis of microglial, stimulating A b clearance.…”
Section: Discussionmentioning
confidence: 99%
“…However, revascularization would be a potential issue for long term treatment of passive immunization, for these therapies could lead to cerebral microhemorrhages related to vascular amyloid deposits [55]. Nevertheless, some monoclonal antibodies have already been tested in AD patients, like solanezumab (LY-2062430), bapineuzumab (AAB-001), and gantenerumab (RG-1450), ponezumab (PF-04360365), GSK-933776, MABT-5102A and immunoglobulins (IVIg) [13].…”
Section: Immunotherapymentioning
confidence: 99%